Prevalence of Cardiovascular Events and Their Risk Factors in Patients With Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnea Overlap Syndrome - Tang, Manyun; Long, Yunxiang; Liu, Shihong; Yue, Xin; Shi, Tao (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective: To determine the prevalence of cardiovascular events and their risk factors in patients with chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) overlap syndrome (OS). Methods: A total of 74 patients with OS between January 2015 and July 2020 were retrospectively enrolled, and two control groups of 222 COPD-only patients and 222 OSA-only patients pair-matched with respect to age and sex were also enrolled. The prevalence of coronary heart disease (CHD), arrhythmia, heart failure, stroke, pulmonary arterial hypertension (PAH), pulmonary embolism (PTE) and venous embolism of extremities was compared among the three groups, and multivariable logistic regression models were used to screen the risk factors. Results: The patients with OS have a higher prevalence rate of heart failure (10.8% vs 0.5%, 1.4%, respectively) and PAH (31.1% vs 4.5%, 17.1%, respectively) than those with OSA alone or COPD alone (all P<0.01). The prevalence of CHD was also significantly higher in the OS group compared with the COPD group (25.7% vs 11.7%, P<0.01). However, there was no significant difference in the prevalence of arrhythmia in three groups (20.3%, 22.5%, 13.1%, respectively. P>0.05). In patients with OS, risk factors for CHD included hypertension, diabetes, BMI, lactate dehydrogenase (LDH) and tidal volume (TV), risk factors for heart failure included diabetes, PO2, PCO2, maximum ventilatory volume (MVV) and neutrophilic granulocyte percentage, risk factors for PAH included minimum nocturnal oxygen saturation (minSpO2), PCO2, BNP and LDH. Conclusions: Patients with overlap syndrome has a higher prevalence of cardiovascular events, the hypoxemia and hypercapnia were associated with an increased risk of cardiovascular events.